Desenvolvimento da estrutura robótica atuada por cabos para reabilitação bimanual do corpo humano - Alves, Thiago (2019)
Stroke is the leading cause of disability in adults worldwide. Robotic rehabilitation therapy enables high-dosage and high-intensity training, improving motor function and functional outcomes. This work presents a cable-driven robot for stroke rehabilitation. The possible setups for this device are unilateral (1 or 2 DOF), bilateral or bimanual, acting in a linear or planar trajectory that can be taught (teaching-by-demonstration). Several serious games were developed together with this device to motivate the patient within the rehabilitation exercises. During the bimanual game play, movement is hampered if there is no use of both arms and an assist-as-needed control changes the amount of assistance based on patient performance and progress. A device validation was performed, and the results showed high accuracy and repeatability levels. A software (BiEval) was developed to evaluate the patient's performance/progress based on quantifiable measures. Fifteen healthy volunteers received exercises using the bimanual device. The level of motivation was measured for healthy and post-stroke volunteers by the Intrinsic Motivation Inventory (IMI), and indicated positive ratings in the dimensions: high interest, high competence and low pressure. Ten stroke patients, 5 chronic stroke and 5 with acute stroke (6±2.1 months after stroke) received 2-3 training sessions each week, during a period of 5 weeks. The training session was composed of bimanual robotic therapy with the MineCart game (30 minutes) in addition to traditional therapy (50 minutes). Two patients reported fatigue and dropped out of the intervention; they were excluded from pos-intervention evaluation. Comparing the first vs. last rehabilitation training session, seven patient’s performance parameters were significant improved. In this way, the proposed structure can be a tool to be used together the conventional physiotherapy.